Engineering laws of the Philippines with related laws - Rex Editorial Staff (Manila, Philippines : Philippine Graphic Arts, 1981)
This book contains the various engineering laws and related laws. Laws that have engineering aspects like the water code, code of sanitation, fire code, laws on environmental planning and pollution are included in this book.
Presidential decree no.223, creating the professional regulation commission -- Civil engineering law -- Mechanical engineering law -- Electrical engineering law -- Chemical engineering law -- Mining engineering law -- Naval Architecture and marine engineering law -- Sanitary engineering law -- Electronics and communications engineering law -- Metallurgical engineering law.
Keywords: ENGINEERING LAW; PHILIPPINES